Juvenile Angiofibroma: Current Management Strategies - Safadi, Ahmad; Schreiber, Alberto; Fliss, Dan M.; Nicolai, Piero (Journal of Neurological Surgery Part B: Skull Base, 2018)
Juvenile angiofibroma (JA) is a benign, highly vascular tumor which is diagnosed on the basis of clinical and imaging features. It has a characteristic pattern of spread commonly involving the pterygopalatine fossa and pterygoid base. The mainstay of treatment is surgery, while radiotherapy is rarely used for the treatment of recurrent lesion. Endoscopic endonasal surgery is currently the treatment of choice for small to intermediate size JAs, and is feasible even for advanced lesions; however, this should only be practiced in well-experienced centers.
Keywords: juvenile angiofibroma; endoscopic surgery; surgical treatment of juvenile angiofibroma